Graphitic carbon nitride doped copper–manganese alloy as high–performance electrode material in supercapacitor for energy storage - Siwal, Samarjeet Singh; Zhang, Qibo; Sun, Changbin; Thakur, Vijay Kumar (MDPI, 2019)
Here, we report the synthesis of copper–manganese alloy (CuMnO2) using graphitic carbon nitride (gCN) as a novel support material. The successful formation of CuMnO2-gCN was confirmed through spectroscopic, optical, and other characterization techniques. We have applied this catalyst as the energy storage material in the alkaline media and it has shown good catalytic behavior in supercapacitor applications. The CuMnO2-gCN demonstrates outstanding electrocapacitive performance, having high capacitance (817.85 A·g−1) and well-cycling stability (1000 cycles) when used as a working electrode material for supercapacitor applications. For comparison, we have also used the gCN and Cu2O-gCN for supercapacitor applications. This study proposes a simple path for the extensive construction of self-attaining double metal alloy with control size and uniformity in high-performance energy-storing materials
Keywords: copper-manganese alloy; energy storage; supercapacitor; graphitic carbon nitride